Eliminating buyer`s remorse: An examination of the sunk cost fallacy in the National Hockey League draft - Farah, L.; Baker, J. (Scandinavian Journal of Medicine & Science in Sports, 2021)
The sunk cost effect describes the tendency to escalate one's commitment toward a certain endeavor, despite diminishing returns, as a consequence of irreversible resource expenditure that has already been made (Organ Behav Hum Decis Process. 1985;35:124). This effect has been observed in a number of professional sports leagues, wherein teams escalate their commitment toward players selected early in the draft, regardless of performance outcomes, due to large financial commitments invested in them (J Sports Econom. 2017;18:282; Adm Sci Q. 1995;40:474). This effect, however, has yet to be explored in the National Hockey League (NHL). The purpose of this study was to test for sunk cost effects in the NHL, by examining the relationship between draft order and playing time, while controlling for a myriad of confounding variables. Findings from our analyses provide support for the existence of this effect in the NHL, as first-round draftees were given significantly more playing time than their peers selected in the second round, regardless of injury, player relocation, penalties, or on-ice performance outcomes. We offer some plausible underlying mechanisms driving this effect. Furthermore, we suggest the observed effects have valuable implications for NHL talent development, given the importance of playing time on various aspects of expertise attainment.